ESC guidelines on stable chest pain: a comparison of the previous and current risk scores for the assessment of pre-test probability of coronary artery disease. (25th November 2020) - Fyyaz, S; Olabintan, O; David, S; Plein, S; Alfakih, K
Abstract: Introduction: The European Society of Cardiology (ESC) guidelines on stable chest pain recommend the use of a pre-test probability (PTP) risk score (RS) which predicts the likelihood of coronary artery disease (CAD) to guide investigation and modality. The 2019 guidelines provide an updated PTPRS compared with 2013 guidelines, adjusted for the lower prevalence of coronary artery disease in contemporary populations. We assessed the performance of the two PTPRS in a cohort of patients with stable chest pain who underwent CT coronary angiography (CTCA) as the first line investigation. Methods: We retrospectively searched a radiology database from January 2017 to June 2018. CTCA reported CAD degree of stenosis as normal/minimal stenosis, mild (30–50%), moderate (50–70%), or severe (>70%) and retrospectively calculated ESC PTP scores for 2013 and 2019 guidelines. Results: In total 652 patients underwent CTCA (mean age 55 yrs; IQR 48–63; 330 male). For ESC 2019 PTPRS there were no patients with PTP >85%. 2 patients had PTP 50–85%; 1 patient had moderate stenosis and 1 mild stenosis on CTCA. 267 patients had PTP 15–50%; 23 (9%) had severe stenosis and 35 (13%) moderate stenosis. Finally, 379 patients had PTP <15%; 11 (3%) had severe stenosis and 18 (5%) moderate CTCA stenosis. In comparison, ESC 2013 PTPRS had 2 patients with PTP >85%; 1 had moderate stenosis and 1 had mild stenosis on CTCA. 149 patients had PTP 50–85%; 17 (11%) had severe stenosis and 23 (15%) moderate stenosis. A further 427 patients had a PTP 15–50%; 17 (4%) had severe stenosis and 32 (8%) had moderate stenosis. Lastly, 70 patients had a PTP <15% and two (3%) were found to have a moderate stenosis on CTCA. Conclusions: The updated ESC 2019 PTPRS appears to underestimate the presence of CAD given 11 (3%) patients with severe CTCA stenosis would have been missed. Although the 2013 PTPRS was thought to overestimate the prevalence of CAD, it did not miss anyone found to have severe CTCA stenosis. Furthermore, patients with evidence of mild or moderate CAD on CTCA may not have been investigated due to PTP <15% and therefore may not be commenced on medical therapy, to derive a mortality benefit as demonstrated in SCOT-Heart trial. Funding Acknowledgement: Type of funding source: None